Evaluation of median nerve in carpal tunnel syndrome by high frequency ultrasound and color Doppler - Krishanan, Priyanka; Joseph, Rani Ann; M., Rakesh (International Journal Of Community Medicine And Public Health, 2025)
Background: Carpal tunnel syndrome (CTS), the most prevalent entrapment neuropathy of the upper limb, frequently leads to pain, numbness, and functional disability. While nerve conduction studies (NCS) remain the diagnostic gold standard, they have notable drawbacks, including patient discomfort and decreased sensitivity in certain populations. As a result, high-frequency ultrasound and color Doppler have emerged as valuable, non-invasive diagnostic tools that offer real-time visualization of structural deformities and vascular alterations in the median nerve, enhancing diagnostic precision in CTS evaluation. Aim and objective of the study was to evaluate the role of high-frequency ultrasound and color Doppler in diagnosing carpal tunnel syndrome. Methods: A comparative cross-sectional study was conducted over 9 months in the Department of Radiodiagnosis, Private Medical College, Kerala. 50 clinically suspected CTS patients underwent high-frequency ultrasound and color Doppler evaluation. Parameters assessed included nerve swelling, edema, flattening, palmar bowing, and vascularity. Results: Most participants were aged between 40-50 years (46%), with a higher proportion of females (86%). Sonographic evaluation revealed that 72% of patients had nerve edema, 80% exhibited nerve swelling, and 60% showed nerve flattening. Palmar bowing was present in 42%, while 24% displayed intraneural vascularity. Conclusions: High-frequency ultrasound and color Doppler are reliable, non-invasive tools for diagnosing CTS. These imaging modalities support early detection and aid in effective clinical management of CTS.